2020
DOI: 10.1152/japplphysiol.00480.2019
|View full text |Cite
|
Sign up to set email alerts
|

Decreased atrioventricular plane displacement after acute myocardial infarction yields a concomitant decrease in stroke volume

Abstract: Acute myocardial infarction (AMI) can progress to heart failure, which has a poor prognosis. Normally, 60% of stroke volume (SV) is attributed to the longitudinal ventricular shortening and lengthening evident in the atrioventricular plane displacement (AVPD) during the cardiac cycle, but there is no information on how the relationship changes between SV and AVPD before and after AMI. Therefore, the aim of this study was to determine how SV depends on AVPD before and after AMI in two swine models. Serial cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Of note, extracellular volume quantification was not available in our study population and may have provided prognostic information. Experimental data have shown that reduced AVPD after acute MI yields a concomitant decrease in SV 39 which also helps to understand why ventricular longitudinal shortening would be prognostic in ischemic heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, extracellular volume quantification was not available in our study population and may have provided prognostic information. Experimental data have shown that reduced AVPD after acute MI yields a concomitant decrease in SV 39 which also helps to understand why ventricular longitudinal shortening would be prognostic in ischemic heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, ventricular systole pulls down the atrio-ventricular plane, and it seems reasonable to assume that the displacement of this plane is an expression of the myocardial contractility (Höglund et al, 1988). In support to the notion that Sm is related to myocardial performance there are findings that mitral anulus systolic excursion is reduced in patients with ventricular dysfunction (Grue et al, 2018;Berg et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…1 B). We based this criterion on reports showing that MAPSE from any wall reflects global LV function, not the regional LV function of that wall [ 23 26 ]. Then, we defined monitoring feasibility as how often we could reassess the same wall from the same patient during the ICU protocol.…”
Section: Methodsmentioning
confidence: 99%